Study of Potential and Marine Ecotourism Development at Pasir Jambak Beach Padang City - Putri Hanryani; Syafruddin Nasution; Dessy Yoswaty (Jurnal Natur Indonesia, 2023)
Marine tourism is a tourism activity based on marine aspects in coastal and marine waters Pasir Jambak Beach is one of the areas that have the potential to be developed into a marine ecotourism object in Padang City. The purpose of this research was to find out the main marine ecotourism object owned by Pasir Jambak Beach, its support capability, and its development strategy. This research was conducted from July to October 2022 at Pasir Jambak Beach, Pasir Nan Tigo Village, Koto Tangah District, Padang City, West Sumatra Province. The method used was a survey method with the observation of the tourism objects that existed at Pasir Jambak beach, measuring the area large which could be utilized and interviewing the tourism businessmen. The results showed that the main marine ecotourism object of Pasir Jambak Beach is the beauty of the beach scenery with clear waters, clean, fine, and sloping sand, and the phenomenon of sunset. The total carrying capacity that can be physically accepted by Pasir Jambak beach is 26,490 people per day with different activities and times. Based on SWOT analysis, the ecotourism development strategy for Pasir Jambak beach is: (1) Development of marine tourism with the concept of ecotourism (2) Increase tourism promotion and improve the quality of human resources through education and training. (3) Form a special team to supervise marine ecotourism development activities, and develop research and conservation potential (4) Organize counseling on the importance of environmental conservation, the dangers of pollution, natural disaster management, and the development of creative industries.